The Effect of Dentist’s Attire on Treatment Acceptance in Children - Jafarzadeh, Mehdi; Azamian, Zeinab; Heidari, Gholamreza (Journal of Dental School, 2019)
Objectives: While great advances have been made in the field of pediatric dentistry, creating a friendly relationship with pediatric patients and getting them to readily accept dental treatment and cooperate remains challenging. Cooperation by children can affect the quality of dental visit and the required time for the treatment. Dentists’ attire could be one of the factors that significantly affect children’s cooperation. The aim of this study was to assess children’s preferences towards dentists’ attire and to determine the influence of its design, color, and other factors on treatment acceptance. Methods: A total of 103 children aged between 6-12 years were randomly divided into three groups (68 children in two study groups and 35 children in one control group). The children were examined by the pediatric dentists wearing different attires. Two questionnaires were designed; one was supposed to be answered by the parents before the dental visit and one by the children after the visit. Results: The majority of children preferred the shirts that were adorned with Winnie the Pooh, while the treatment acceptance was not significantly different between the groups. Sex, age, number of family members, birth order, patient’s personality type, and parents’ educational level had no significant impact on treatment acceptance. Conclusion: Although the attire design did not significantly affect treatment acceptance, it helped to establish a good relationship with pediatric patients in their first visit. The results help pediatric dentists choose attire that are better received by pediatric patients.